Ajuste fiscal no Brasil: Os limites do possível - Sérgio Wulff Gobetti (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This text aims to qualify the debate on the need for fiscal adjustment in Brazil, showing that the trend that takes place - at this conjuncture, as in other past - a low quality setting, based on cutting investments and / or increased tax burden, it is almost inevitable in the face of public expenditure structure, both in terms of composition and dynamics. The empirical analysis is based on a methodology of decomposition of the primary balance of the central government with the help of the Integrated Financial Management System information (Siafi), which identifies its main determinants vectors - in terms of revenue and expenditure - and investigate further the recent increase in so-called "other current and capital expenses" (OCCs). One of prescriptive conclusions of the text is that the government should avoid a hard adjustment in the short term that would undermine the resumption of economic growth and prioritize a medium and long-term reform agenda capable of improving the tax system and signal the possibility of structural improvements in fiscal results.
Keywords: E62; H62; H53; 330; fiscal adjustment; primary surplus; expansionary contractions